KINERJA FINANSIAL DAN KESEMPATAN INVESTASI PERUSAHAAN BERTUMBUH DAN TIDAK BERTUMBUH - Puspitasari, Novi (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2012)
The purpose of this study are : (1) to analyze the influence of financialperformance against IOS of growing company and ungrowing company, (2) toanalyze the influence of the financial performance of the IOS of growing in crisisand recovery crisis, (3) to analyze influence the financial performance ofungrowing companies on IOS in crisis and post crisis period.This study uses theparadigm of positive quantitative analysis by using common factor analysis (CFA)and multiple regression analysis. The first results show that there are differences inthe influence of financial performance against IOS of growing and ungrowingcompanies. The second result shows that there are differeness influence offinancial performance of growing company IOS in crisis and post-crisis conditions.And the third results found that there is no significant differences influence thefinancial performance of ungrowing companies IOS on the crisis and post-crisisperiod.